Detection and Tracking Strategies for Autonomous Aerial Refuelling Tasks Based on Monocular Vision. (9th July 2014) - Yin, Yingjie; Xu, De; Wang, Xingang; Bai, Mingran
Detection and tracking strategies based on monocular vision are proposed for autonomous aerial refuelling tasks. The drogue attached to the fuel tanker aircraft has two important features. The grey values of the drogue's inner part are different from the external umbrella ribs, as shown in the image. The shape of the drogue's inner dark part is nearly circular. According to crucial prior knowledge, the rough and fine positioning algorithms are designed to detect the drogue. Particle filter based on the drogue's shape is proposed to track the drogue. A strategy to switch between detection and tracking is proposed to improve the robustness of the algorithms. The inner dark part of the drogue is segmented precisely in the detecting and tracking process and the segmented circular part can be used to measure its spatial position. The experimental results show that the proposed method has good performance in real-time and satisfied robustness and positioning accuracy.